Mesh-less method for homogeneous handling of fiber-fluid interactions - Marheineke, Nicole (Computational Fluid and Solid Mechanics, 2003)
The motion of flexible fibers suspended in an incompressible flow is of interest to researchers in various fields, e.g. composite materials, biotechnology, paper and fashion industry. In this work, a single one-dimensional fiber in a two-dimensional flow field is considered. Embedding the fiber's dynamic into a mesh-less flow concept (particle scheme) via a partition of unity method promises to be an elegant way to describe their interactions. The construction of PUM spaces in dependence on the flow test spaces results in an adoption of the flow resolution and a simplification of the representation of the acting forces. On the other hand, the consequences of time-dependent approximation spaces have to be accepted.
Keywords: Flexible fibe; Fluid-structure interaction; Galerkin method; Mesh-less method; Particle scheme; Partition of unity method; PUM space